The effect of recanalization on long‐term neurological outcome after cerebral venous thrombosis. (8th February 2018) - Rezoagli, E.; Martinelli, I.; Poli, D.; Scoditti, U.; Passamonti, S. M.; Bucciarelli, P.; Ageno, W.; Dentali, F.
Abstract : Essentials The role of cerebral venous thrombosis (CVT) recanalization on neurologic outcome is still debated. We studied a large cohort of 508 CVT patients with 419 patient years of radiological follow‐up. Recanalization rate is high during the first months after CVT and neurologic outcome is favorable. High recanalization grade of CVT independently predicts good neurological outcome. Summary: Background: Studies with limited sample size and with discordant results described the recanalization time‐course of cerebral venous thrombosis (CVT). The neurological outcome after a first episode of CVT is good, but the role of recanalization on neurological dependence is still debated. Objectives: The aim of the study is to assess the recanalization rate after cerebral venous thrombosis (CVT) and its prognostic role in long‐term neurological outcome. Patients/Methods: In a retrospective observational multicenter cohort study, patients with an acute first episode of CVT with at least one available imaging test during follow‐up were enrolled. Patency status of the vessels was categorized as complete, partial or not recanalized. Neurological outcome was defined using the modified Rankin scale (mRS) as good (mRS = 0–1) or poor (mRS = 2–6). Results: Five‐hundred and eight patients (median [IQR] age, 39 [28.5–49] years; 26% male) were included. Complete or partial recanalization was not differently represented in patients undergoing scans at different periods of time (from 28‐day to 3 month‐period up to a 1–3 year‐period). mRS at the time of follow‐up imaging was available in 483 patients; 92.8% of them had a mRS of 0‐1. CVT recanalization (odds ratio [OR], 2.56; 95% confidence interval [CI], 1.59–4.13) was positively associated, whereas cancer (OR, 0.29; 95% CI, 0.09–0.88), and personal history of venous thromboembolism (VTE) (OR, 0.36; 95% CI, 0.14–0.92) were negatively associated as independent predictors of favorable (mRS = 0–1) outcome at follow‐up. Conclusions: Most patients with a first CVT had complete or partial recanalization at follow‐up. Recanalization was independently associated with a favorable neurological outcome.